A kinetic study of methane hydrate formation in the corn Cobs + Tetrahydrofuran solution system. (15th October 2021) - Yu, Yi-Song; Zhang, Qing-Zong; Chang-Chen; Lv, Qiu-Nan; Zhou, Shi-Dong; Yi, Wen-Zhe; Li, Xiao-Sen
Highlights: Synergistic effect of corn cob and THF on CH4 hydrate formation is studied. The CH4 uptake as high as 98.09 mmol/mol H2 O is obtained from this work. Two stages of CH4 hydrate formation are observed in the system. Both 5 12 and 5 12 6 4 cages of sII are ocScupied by CH4 molecules. Abstract: A porous medium with a high specific surface area can be used to promote hydrate formation. In this work, the kinetics of methane (CH4 ) hydrate formation in the presence of corn cobs and Tetrahydrofuran was systematically studied by determining the hydrate formation process, induction time, gas uptake, and hydrate formation rate. The results showed that hydrates form immediately as the CH4 loading and the multi-stage of hydrate formation is observed. Relative to THF solutions, the addition of corn cobs has a positive effect on CH4 uptake at THF concentrations <= 3.0 mol%. The optimum conditions of CH4 hydrate formation in this work is corn cobs + THF (3.0 mol%) solution. In these conditions, the highest final gas uptake, approximately 98.40 ± 6.26 mmol/molH2 O, and the shortest time required to achieve 90% of this gas uptake, approximately 3.12 h, is achieved. Besides, though the conditions adopted in this work are above the phase equilibrium of sI CH4 hydrate formation, only sII hydrates are observed in this work. Meanwhile, except at the stoichiometric THF concentration of 5.6 mol%, it was confirmed that CH4 molecules are not only trapped in the 5 12 cages of sII but also encaged in the 5 12 6 4 cages of sII.